The Impact of Contextual Connotation on the Investigations of Fundamentalists and the Purposes of Sharia - Werdee , Mushtaq (Islamic Sciences Journal, 2023)
ABSTRACT In the course of their books, fundamentalists talked about the connotation of the context and its obvious impact on building the fundamentalist base. Many recent studies have researched the types of this Connotation and its influence on the understanding of texts. Some studies have neglected, according to the researcher, the views of fundamentalists and their jurisprudence in guiding contextual significance, and how they directed this connotation commensurate with the purposes of the Sharia, which called the researcher to indicate the views of fundamentalists and their words in the semantics of the context of the texts of legitimacy, and then build these rules which were developed by scientists and directed guidance to achieve the legitimate purpose behind these provisions. Thuse the research was divided into four chapters: The first chapter: the definition of connotation language and idiomatic. The second chapter: the concept of context in the language and the term scientists. The third chapter: Contextual connotation in the fundamentalists. The fourth chapter: contextual connotation and the purposes of Sharia.